Emplacing Indigeneity and rurality in neoliberal disability welfare reform: The lived experience of Aboriginal people with disabilities in the West Kimberley, Australia - Soldatic, Karen; Somers, K.; Spurway, K.; van Toorn, G. (Pion Limited, 2017)
© 2017, © The Author(s) 2017. This article maps the impact of neoliberal restructuring of disability services and income support measures on Aboriginal people with disabilities living in rural areas of the West Kimberley in Australia. The international literature has extensively documented disability and Indigenous neoliberal welfare retraction measures, though as discrete areas of research. We aim to emplace the intersectional experience of such reforms by exposing their unique and qualitatively different dynamics and processes of disablement and Indigenous dispossession in the lived experiences of Aboriginal Australians with disabilities in rural Australia. Interviews conducted with Aboriginal people with disabilities living in the West Kimberley revealed the impact of neoliberal policies of retracting disability supports and rationalising services. The effects were felt in terms of people’s mobility, autonomy and economic security, with chronic, and at times crisis, levels of socio-economic insecurity experienced. Neoliberal spatial structures have led to further peripheralisation of rural and remote populations and a resulting increase in levels of inequality, deprivation and marginalisation for Aboriginal Australians with disabilities, who endure and survive by navigating these disabling spaces.